Tunable electrical resistance of polyaniline and its correlation to morphological properties and surface functional groups. Issue 6 (17th February 2023) - Koh, Wee Siang; Khaw, Liang Fa; Yeap, Swee Pin; Lee, Kiat Moon; Sum, Jing Yao; Toh, Pey Yi
Abstract: Polyaniline (PANI) is a conductive polymer that is attracting much attention nowadays especially for the design of flexible supercapacitors and sensors. One of the commonly used methods to synthesize PANI is chemical oxidative polymerization (COP). In the present work, the effects of (i) polymerization time and (ii) type of dopant media used in COP were evaluated and correlated to the morphological and electrical properties of the formed PANI. In terms of morphological properties, it was found that extending the polymerization time of COP in hydrochloric acid (HCl) medium from 1 to 5 h induced the formation of regular flake‐ and globule‐like structures. Despite that, there was not much change in the surface functional groups, as verified from the infrared absorption spectrum. An intermingled structure containing (i) stacking of flake‐like particles and (ii) interconnection of long fibrous‐like particles with fewer branches was seen for PANI produced at 3 h of polymerization time. Such a unique morphological property is suggested to lower the electrical resistance of PANI to 0.56 × 10 3  Ω. On the other hand, by changing the dopant medium from HCl to sulfuric acid (H2 SO4 ), acetic acid (CH3 COOH), water (H2 O) and ammonium hydroxide (NH3 ⋅H2 O), the PANI morphology was altered to globular shape with cauliflower‐like structure, tube‐like structure, plate‐like structure and flake‐like structure, respectively. The resistance of these PANIs was successfully tuned and found to increase following the order of PANI–H2 SO4  < PANI–CH3 COOH < PANI–H2 O < PANI–NH3 ⋅H2 O. © 2023 Society of Industrial Chemistry. Abstract : The electrical resistance of PANI was tuned by manipulating the polymerization time and the type of dopant media. A polymerization time of 3 h in HCl produced PANI with the lowest electrical resistance. The low resistance was attributed to stacking of flake‐like particles and interconnection of long fibrous‐like particles with fewer branches.